Proceedings of the ACM Multimedia 2012 Workshop on Multimedia for Cooking and Eating Activities 2012
DOI: 10.1145/2390776.2390789
|View full text |Cite
|
Sign up to set email alerts
|

Recipe sub-goals and graphs

Abstract: Following recipes can be difficult for cooks. Many recipes use technical culinary language and condense their instructions into brief sentences, cooks may also get lost in long paragraphs as they jump around the recipe to find tasks to perform in parallel. Multimedia content has been shown to increase the confidence of cooks but few comparative evaluations have been reported. In this study we evaluated the effect of adding pictures of interim goal states to a plain text recipe and the effect of presenting reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The format in which the recipe is presented, whether it be through text, video, or a combination of both, significantly impacts the learning experience during the cooking process [28][29][30][31][32]. Videos have been perceived to help over and above recipe cards through improved comprehension, real-time reassurance, and enjoyment of the cooking process, as well as the acquisition of new cooking skills [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The format in which the recipe is presented, whether it be through text, video, or a combination of both, significantly impacts the learning experience during the cooking process [28][29][30][31][32]. Videos have been perceived to help over and above recipe cards through improved comprehension, real-time reassurance, and enjoyment of the cooking process, as well as the acquisition of new cooking skills [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, research has rarely examined the use of recipe cards on cooking motivation and skills. Buykx et al (2013) found that recipe cards, with their concise format and easy-tofollow instructions, significantly improved cooking skills among novices [29]. Furthermore, Liu et al [37] provided three interventions: food samples, recipe cards, and promotional discounts on fruits and vegetables, and found that recipe cards were significantly associated with the frequency of fruit and vegetable consumption.…”
Section: Introductionmentioning
confidence: 99%